correctly select the order of the steps to solve this equation

1/3(6x - 9) = -33

1 answer

To solve the equation \(\frac{1}{3}(6x - 9) = -33\), you can follow these steps in order:

  1. Multiply both sides by 3 to eliminate the fraction: \[ 6x - 9 = -99 \]

  2. Add 9 to both sides to isolate the term with \(x\): \[ 6x = -90 \]

  3. Divide both sides by 6 to solve for \(x\): \[ x = -15 \]

So the order of the steps is:

  1. Multiply both sides by 3.
  2. Add 9 to both sides.
  3. Divide both sides by 6.